Ácido quinolínico e neurodegeneração glutamatérgia em Caenorhabditis elegans - Silveira, Tássia Limana da (2019)
Quinolinic acid (QUIN) is an endogenous neurotoxin that acts as an N-methyl-D-aspartate receptor (NMDAR) agonist generating a toxic cascade, which can lead to neurodegeneration. The action of QUIN in Caenorhabditis elegans and the neurotoxins that allows the study of glutamatergic system disorders have not been carefully addressed. The effects of QUIN on toxicological and behavioral parameters in VM487 (nmr-1) and VC2623 (nmr-2) mutants strains, as well as in wild-type (WT) animals were performed to evaluate whether QUIN could be used as a neurotoxin in C. elegans. QUIN reduced survival of WT worms in a dose-dependent manner. A sublethal concentration of QUIN (20 mM) increased reactive oxygen species (ROS) levels in a nmr-1/NMDAR-dependent manner, activated the DAF-16/FOXO transcription factor, and increased expression of the proteins, as the superoxide dismutase-3, Glutathione S-transferase-4, and heat shock protein-16.2. QUIN did not change motor behavioral parameters but altered the sensory behavior in WT and VM487 (nmr-1) worms. Notably, the effect of QUIN on the sensory behavioral parameters might occur, at least in part, secondary to increased ROS. However, the touch response behavior indicates a mechanism of action independent of ROS generation. In addition, the non-lethal concentration of QUIN can have unleashed possible neurodegeneration in the glutamatergic system considering the relation between the behavioral data and the GFP-neuronal measures. Our findings indicate that C. elegans have a QUIN mechanism like that found in organisms like mammals, indicating that it can be useful to studies with the glutamatergic system. Thus, the C. elegans can be used more specifically in diseases that have among their etiologies the glutamatergic excitotoxicity as in mammals.